Efektivitas Zoom sebagai Platform Pembelajaran Hybrid dalam Meningkatkan Partisipasi Mahasiswa - Fatwa Arrevi; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
In the current digital era, hybrid learning has emerged as an effective method in higher education. With the rapid adoption of online learning tools during the COVID-19 pandemic, Zoom has become a popular choice for educational institutions. This study aims to evaluate the effectiveness of Zoom as a hybrid learning platform in increasing student participation. Through a mixed-methods approach, including surveys, interviews, and participation data analysis, we explored how Zoom's features impact student engagement in a hybrid learning environment. Findings indicate that interactive features such as breakout rooms and polling contribute to increased student participation. However, technical issues and digital fatigue remain challenges. This research provides valuable insights for educators and institutions seeking to optimize hybrid learning experiences and enhance student engagement.